Komitmen Terhadap Organisasi Karyawan UKM Kuliner: Sistematis Literatur Review Pengaruh Rasa Dukungan Organisasi, Kreativitas, Motivasi Kerja - Elizabeth, Roosganda; Notosudjono, Didik; Yusnita, Nancy; Hamzah, Hamzah; Sunaryo, Widodo; Margaretha, Giovanni Inez Erika; Ivan, Geraldy Samuel (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The weakening of the existence of Culinary SMEs in Bogor has been identified, due to various factors, one of which is the research objective of this Systematic Literature Review, namely identifying, analyzing and exploring the factors that influence commitment to the organization in culinary SMEs in Bogor, with a focus on organizational support, creativity, and predicted work motivation are some of the influencing factors. Through a systematic literature review method, (SRL) this article identifies, analyzes and explores how each of these factors contributes to increasing organizational commitment and facing challenges in maintaining the existence of culinary SMEs. The research results show that strong organizational support, high creativity and good work motivation can significantly increase commitment to the organization, which in turn helps strengthen the existence of culinary SMEs in Bogor.